Dynamic Model of Land Use Change in Landslide Hazard Zones in Tanah Datar District, West Sumatra - Dewata, Indang (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
Population growth has an impact on land resource needs, pressure on land use will have an impact on environmental degradation. As an effort to reduce pressure, policy efforts in land use are needed. This study aims to develop dynamic models in land use and develop land use policy direction.The method used in dynamic modeling uses system analysis and land change policy direction using ISM analysis. In dynamic modeling, land use change uses three scenarios, namely: optimistic scenario, muder scenario, and pessimistic scenario. In determining the direction of the policy involving all stakeholders as many as 15 experts. The results of dynamic model analysis show that forest area changes from time to time of 1.6 percent per year. Changes in forest areas will have an impact on increasing environmental disasters. As an effort to save the environment, there is a need for law enforcement and strict sanctions against perpetrators of forest area destruction